(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Proteus syndrome is a very complex and rare to find in the world. It consists of asymmetric and disproportionate overgrowth in bones and skins. There are very few cases that have been come in light all over the world. The responsible genes for the proteus syndrome were AKT1 gene and PTEN. AKT1 is causing of proliferation, growth in cell cycle and PTEN is tumour suppressor gene in which the change causes the growth in cells. Proteus syndrome is a mutation occurs in chromosomes and it is a disorder not a disease. The major breaks of pathway are commonly found and eventually lead to the clinical approaches as their effect.